Strategies for the drug treatment of depression. - Cooper, A. J. (1984)
Antidepressants are a useful addition to a physician's therapeutic armamentarium, but because they are used to treat disorders of diverse and largely unknown cause, there is a much greater element of chance associated with their use than with the use of many other types of drugs (e.g., antibiotics and analgesics). Nevertheless, empirically derived treatment schemes, applied systematically, increase the odds of a favourable response and are preferred to haphazard prescribing. To date, no one antidepressant has been shown to be more effective than any other, although the newer agents are alleged to be faster acting, more specific and less toxic than the established drugs. However, generally, such claims have not been proven clinically. Unless there are overwhelming contraindications (e.g., intolerable side effects, an idiosyncratic response or coexisting cardiac disease) the established agents, with their proven efficacy, are preferred initially.